Bias Evaluation of the Accuracy of Two Extraoral Scanners and an Intraoral Scanner Based on ADA Standards. (11th June 2021) - Cui, Naiyu; Wang, Jiayin; Hou, Xingyu; Sun, Shixun; Huang, Qixuan; Lim, Ho-Kyung; Cai, HongXin; Jia, Qi; Lee, Eui-Seok; Jiang, Heng Bo
Abstract : The spread and application of computer-aided design/computer-aided manufacturing (CAD/CAM) technology have contributed to the rapid development of digitalization in dentistry. The accuracy of scan results is closely related to the devising subsequent treatment plans and outcomes. Professional standards for evaluating scanners are specified in the American National Standard/American Dental Association Standard 132 (ANSI/ADA No. 132). The aims of this study were to use the three samples mentioned in ANSI/ADA No. 132 and evaluate the accuracy and reproducibility of two extraoral scanners and an intraoral scanner based on the inspection standards recommended by ANSI/ADA No. 132. In this study, two trained operators used two extraoral scanners (E4, 3Shape, Denmark & SHINING DS100+, Shining, China) and an intraoral scanner (TRIOS SERIES3, 3Shape, Denmark) to perform 30 scans of each of the three samples at a temperature of 25 ± 2 ° C and export standard tessellation language files and used reverse engineering software to perform measurements and iterative nearest point matching experiments. The measured values obtained were compared with the reference values measured by a coordinate measuring machine (NC8107, Leader Metrology, USA). We performed a normal distribution test (Shapiro-Wilk test), the nonparametric Kruskal-Wallis test, and an independent-samples t -test to analyze the reproducibility of each scan for different models. The experimental results indicate that the trueness and precision of the two extraoral scanners and the intraoral scanner had a slight mean deviation. The trueness and precision of the three scanners on the curved surface and groove areas are poor. The accuracy and reproducibility of E4 outperformed SHINING and TRIOS. The iterative closest point matching experiment also showed good matching results. The two extraoral scanners and the intraoral scanner in this study can meet the basic clinical requirements in terms of accuracy, and we hope that digital technology will be more widely used in dentistry in the future.